2013
DOI: 10.1159/000343282
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy ± Cetuximab Modulates Peripheral Immune Responses in Metastatic Colorectal Cancer

Abstract: Objective: To identify changes in peripheral immune responses in patients with metastatic colorectal cancer (mCRC) treated with irinotecan/5-fluorouracil/leucovorin (IFL) alone or in combination with cetuximab (C-IFL). Methods: Peripheral blood mononuclear cells (PBMCs) collected from healthy donors (n = 20) and patients with mCRC receiving treatment with either IFL (n = 30) or C-IFL (n = 30) were tested for cytokine production upon polyclonal stimulation with anti-CD3 monoclonal antibody, T cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Studies in APC min/+ mice models have revealed a novel EGFR-independent oncogenic signal of EGF in the tumor microenvironment [61]. So, strategies that target immune effectors including CD15/FUT4, LY6G6D/F, CD137, CD73, or NK-activating targets may enhance the efficacy of anti-EGFR therapies (Figure 2) [41,42,63,64,65,66,67,68,69,70]. Furthermore, mCRC patients treated with cetuximab plus chemo-therapy show altered cytokine production by the peripheral blood cells after treatment (specifically, an increase in IL-2, IFN-γ, IL-12, and IL-18, and a decrease in IL-4 and IL-10) which correlated with the response to therapy.…”
Section: Contribution Of Tumor Microenvironment To Acquired Resistmentioning
confidence: 99%
“…Studies in APC min/+ mice models have revealed a novel EGFR-independent oncogenic signal of EGF in the tumor microenvironment [61]. So, strategies that target immune effectors including CD15/FUT4, LY6G6D/F, CD137, CD73, or NK-activating targets may enhance the efficacy of anti-EGFR therapies (Figure 2) [41,42,63,64,65,66,67,68,69,70]. Furthermore, mCRC patients treated with cetuximab plus chemo-therapy show altered cytokine production by the peripheral blood cells after treatment (specifically, an increase in IL-2, IFN-γ, IL-12, and IL-18, and a decrease in IL-4 and IL-10) which correlated with the response to therapy.…”
Section: Contribution Of Tumor Microenvironment To Acquired Resistmentioning
confidence: 99%
“…IL‐18 production was increased in peripheral blood mononuclear cells obtained from colorectal cancer patients who were treated with irinotecan‐based regimens (Xynos et al . ). However, none of the studies outlined here assessed the contributions of IL‐18 to the pathogenesis of intestinal disease.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Leach et al (2008) found increased local and systemic IL-18 and IL-18bp production in patients with inflammatory bowel disease, suggesting that this cytokine may contribute to local inflammatory changes. IL-18 production was increased in peripheral blood mononuclear cells obtained from colorectal cancer patients who were treated with irinotecan-based regimens (Xynos et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, several lines of evidence suggest that CPT-11-triggered diarrhoea is associated with the production of the pro-inflammatory cytokines IL-1β and IL-18 [20], suggesting an immunogenic response. Previous studies have also demonstrated an anticancer effect of CPT-11-associated anti-tumour immunity [21]. Consequently, we consider CPT-11-induced diarrhoea as an ideal model to dissect the mechanism of the interplay between immunogenic response-associated anti-tumour efficacy and the adverse effects of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%